Acute injuries in handball - Luig, P.; Henke, T. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
Analysis of injury statistics and literature review indicates that the overall incidence of acute injuries in handball is around 2/1000h. Match incidences are ten time higher than training incidences. Lower extremities account for most injuries, followed by head injuries and injuries of the upper extremities. Sprains and contusions are leading injury types. Women are more vulnerable for non-contact lower extremity injuries whereas men have a higher share of contact head injuries. Backcourt players seem to be most at risk.